🎉 从330转为WashU帮助手册啦!

Math4111
模块
Math4111 L19

Lecture 19

Review

Binomial theorem: For nNn\in\mathbb{N}, (a+b)n=k=0n(nk)ankbk(a+b)^n=\sum_{k=0}^{n}\binom{n}{k}a^{n-k}b^k

  1. Show that 2n(n4)2^n\geq \binom{n}{4} for all n4n\geq 4. (Hint: Expand (1+1)n(1+1)^n using the binomial theorem) Proof: (1+1)n=k=0n(nk)1nk1k=k=0n(nk)=(n0)+(n1)++(nn)(n4)\begin{aligned} (1+1)^n&=\sum_{k=0}^{n}\binom{n}{k}1^{n-k}1^k\\ &=\sum_{k=0}^{n}\binom{n}{k}\\ &=\binom{n}{0}+\binom{n}{1}+\cdots+\binom{n}{n}\\ &\geq\binom{n}{4} \end{aligned} EOP
  2. Using part 1, show that limnn32n=0\lim_{n\to\infty}\frac{n^3}{2^n}=0.
    Proof: n32nn3(n4)\frac{n^3}{2^n}\leq\frac{n^3}{\binom{n}{4}} The value of n3(n4)\frac{n^3}{\binom{n}{4}} is decreasing when n4n\geq 4. EOP

New materials

Series

Definition 3.21

Let (an)n=1(a_n)_{n=1}^{\infty} be a sequence in C\mathbb{C}. Let sn=k=1naks_n=\sum_{k=1}^{n}a_k denotes the sequence of partial sums.

  1. We say the series n=1an\sum_{n=1}^{\infty}a_n converges if the sequence of partial sums (sn)n=1(s_n)_{n=1}^{\infty} converges.
  2. We define the sum of the series n=1an\sum_{n=1}^{\infty}a_n to be the limit of the sequence of partial sums, i.e., n=1an=limnsn=limnk=1nak.\sum_{n=1}^{\infty}a_n=\lim_{n\to\infty}s_n=\lim_{n\to\infty}\sum_{k=1}^{n}a_k.

Theorem 3.22 (Cauchy criterion for series)

The series n=1an\sum_{n=1}^{\infty}a_n converges if and only if for every ϵ>0\epsilon>0, there exists NNN\in\mathbb{N} such that for all m,nNm,n\in\mathbb{N} with mnNm\geq n\geq N,

k=nmak<ϵ.\left|\sum_{k=n}^{m}a_k\right|<\epsilon.

Proof:

n=1an\sum_{n=1}^{\infty}a_n converges if and only if (sn)n=1(s_n)_{n=1}^{\infty} converges.

Since C\mathbb{C} is complete, (sn)n=1(s_n)_{n=1}^{\infty} converges if and only if (sn)n=1(s_n)_{n=1}^{\infty} is Cauchy.

Since (sn)n=1(s_n)_{n=1}^{\infty} is Cauchy, for every ϵ>0\epsilon>0, there exists NNN\in\mathbb{N} such that for all m,nNm,n\in\mathbb{N} with mnNm\geq n\geq N,

smsn=k=nmak<ϵ.|s_m-s_n|=\left|\sum_{k=n}^{m}a_k\right|<\epsilon.

EOP

Special case of this theorem.

Corollary 3.23

If n=1an\sum_{n=1}^{\infty}a_n converges, then limnan=0\lim_{n\to\infty}a_n=0.

Note: the converse is not true. Example: n=11n\sum_{n=1}^{\infty}\frac{1}{n} diverges.

The contrapositive of this corollary is: If limnan0\lim_{n\to\infty}a_n\neq 0, then n=1an\sum_{n=1}^{\infty}a_n diverges. It is useful naming as ``n-th term test for divergence''.

Observe:

n,an0\forall n,a_n\geq 0

(an)(a_n) is a non-negative sequence if and only if (sn)n=1(s_n)_{n=1}^{\infty} is increasing sequence.

So if (an)(a_n) is a non-negative sequence, then n=1an\sum_{n=1}^{\infty}a_n converges if and only if (sn)n=1(s_n)_{n=1}^{\infty} is bounded above.

Theorem 3.25 (Comparison test)

Let (an)(a_n) be a sequence in C\mathbb{C} and (cn)(c_n) be a non-negative sequence in R\mathbb{R}. Suppose n,ancn\forall n, |a_n|\leq c_n.

(a) If the series n=1cn\sum_{n=1}^{\infty}c_n converges, then the series n=1an\sum_{n=1}^{\infty}a_n converges.
(b) If the series n=1an\sum_{n=1}^{\infty}a_n diverges, then the series n=1cn\sum_{n=1}^{\infty}c_n diverges.

Proof:

(a) By Theorem 3.22, it's enough to show that for every ϵ>0\epsilon>0, there exists NNN\in\mathbb{N} such that for all m,nNm,n\in\mathbb{N} with mnNm\geq n\geq N,

k=nmak<ϵ.\left|\sum_{k=n}^{m}a_k\right|<\epsilon.

Let ϵ>0\epsilon>0 be arbitrary.

Since n=1cn\sum_{n=1}^{\infty}c_n converges, by Theorem 3.22, for the above ϵ\epsilon, there exists NNN\in\mathbb{N} such that for all m,nNm,n\in\mathbb{N} with mnNm\geq n\geq N,

k=nmckk=nmck<ϵ.\left|\sum_{k=n}^{m}c_k\right|\leq \sum_{k=n}^{m}c_k<\epsilon.

EOP

Theorem 3.26 (Geometric series)

Let xCx\in\mathbb{C}.

(a) If x<1|x|<1, then the series n=0xn\sum_{n=0}^{\infty}x^n converges and n=0xn=11x\sum_{n=0}^{\infty}x^n=\frac{1}{1-x}.
(b) If x1|x|\geq 1, then the series n=0xn\sum_{n=0}^{\infty}x^n diverges.

Proof:

(b) If x1|x|\geq 1, then xnx^n does not converge to 0. So the series n=0xn\sum_{n=0}^{\infty}x^n diverges.

(a) Let sn=k=0nxk=1+x+x2++xns_n=\sum_{k=0}^{n}x^k=1+x+x^2+\cdots+x^n.

xsn=x+x2+x3++xn+xn+1=sn+xn+1xs_n=x+x^2+x^3+\cdots+x^n+x^{n+1}=s_n+x^{n+1}.

So sn=1xn+11xs_n=\frac{1-x^{n+1}}{1-x}.

Since x<1|x|<1, xn+1x^{n+1} converges to 0. So limnsn=11x\lim_{n\to\infty}s_n=\frac{1}{1-x}.

EOP

Lemma 3.28

(a) n=01n\sum_{n=0}^{\infty}\frac{1}{n} diverges.
(b) n=01n2\sum_{n=0}^{\infty}\frac{1}{n^2} converges.

Proof:

(a)

n=01n=11+12+(13+14)+(15+16+17+18)+>12+12+(14+14)+(18+18+18+18)+=12+12+12+12+=\begin{aligned} \sum_{n=0}^{\infty}\frac{1}{n}&=\frac{1}{1}+\frac{1}{2}+\left(\frac{1}{3}+\frac{1}{4}\right)+\left(\frac{1}{5}+\frac{1}{6}+\frac{1}{7}+\frac{1}{8}\right)+\cdots\\ &>\frac{1}{2}+\frac{1}{2}+\left(\frac{1}{4}+\frac{1}{4}\right)+\left(\frac{1}{8}+\frac{1}{8}+\frac{1}{8}+\frac{1}{8}\right)+\cdots\\ &=\frac{1}{2}+\frac{1}{2}+\frac{1}{2}+\frac{1}{2}+\cdots\\ &=\infty \end{aligned}

(b)

n=01n2=11+122+132+142+<11+(122+122)+(142++142)+(182++182)+=11+222+442+882+=11+122+123+124+=1112=112=2\begin{aligned} \sum_{n=0}^{\infty}\frac{1}{n^2}&=\frac{1}{1}+\frac{1}{2^2}+\frac{1}{3^2}+\frac{1}{4^2}+\cdots\\ &<\frac{1}{1}+\left(\frac{1}{2^2}+\frac{1}{2^2}\right)+\left(\frac{1}{4^2}+\cdots+\frac{1}{4^2}\right)+\left(\frac{1}{8^2}+\cdots+\frac{1}{8^2}\right)+\cdots\\ &=\frac{1}{1}+\frac{2}{2^2}+\frac{4}{4^2}+\frac{8}{8^2}+\cdots\\ &=\frac{1}{1}+\frac{1}{2^2}+\frac{1}{2^3}+\frac{1}{2^4}+\cdots\\ &=\frac{1}{1-\frac{1}{2}}\\ &=\frac{1}{\frac{1}{2}}\\ &=2 \end{aligned}

Fun fact: n=11n2=π26\sum_{n=1}^{\infty}\frac{1}{n^2}=\frac{\pi^2}{6}.

EOP

Theorem 3.27 (Cauchy condensation test)

Suppose (an)(a_n) is a non-negative sequence. The series n=1an\sum_{n=1}^{\infty}a_n converges if and only if the series k=02ka2k\sum_{k=0}^{\infty}2^ka_{2^k} converges.

Proof:

Let sn=k=1naks_n=\sum_{k=1}^{n}a_k and tk=k=0k2ka2kt_k=\sum_{k=0}^{k}2^ka_{2^k}.

If n2kn\leq 2^k, then

sn=a1+a2++ana1+(a2+a3)+(a4+a5++a7)++(a2k+a2k+1++a2k+11)a1+2a2+4a4++2ka2k=tk.\begin{aligned} s_n&=a_1+a_2+\cdots+a_n\\ &\leq a_1+(a_2+a_3)+(a_4+a_5+\cdots+a_7)+\cdots+(a_{2^k}+a_{2^k+1}+\cdots+a_{2^{k+1}-1})\\ &\leq a_1+2a_2+4a_4+\cdots+2^ka_{2^k}\\ &=t_k. \end{aligned}

If n2k+1n\geq 2^{k+1}, then

sn=a1+a2++ana1+a2+(a3+a4)+(a5+a6++a7)++(a2k+a2k+1++a2k+11)a1+a2+2a4++2k1a2k12(a1+2a2+4a4++2ka2k)=12tk.\begin{aligned} s_n&=a_1+a_2+\cdots+a_n\\ &\geq a_1+a_2+(a_3+a_4)+(a_5+a_6+\cdots+a_7)+\cdots+(a_{2^k}+a_{2^k+1}+\cdots+a_{2^{k+1}-1})\\ &\geq a_1+a_2+2a_4+\cdots+2^{k-1}a_{2^k}\\ &\geq \frac{1}{2}\left(a_1+2a_2+4a_4+\cdots+2^ka_{2^k}\right)\\ &=\frac{1}{2}t_k. \end{aligned}

We have shown that

  • If n2kn\leq 2^k, then sntks_n\leq t_k.
  • If n2k+1n\geq 2^{k+1}, then sn12tks_n\geq \frac{1}{2}t_k.

So (sn)n=1(s_n)_{n=1}^{\infty} is a bounded above.

By Theorem 3.14, (sn)n=1(s_n)_{n=1}^{\infty} converges if and only if (tk)k=0(t_k)_{k=0}^{\infty} converges.

EOP